Advice to use infant formula and free samples are common in both urban and rural areas in China: a cross-sectional survey. Issue 8 (8th June 2021) - Li, Jia; Nguyen, Tuan T; Duan, Yifan; Mathisen, Roger; Yang, Zhenyu
Abstract: Objective: To examine the association between the place of residence and receiving free samples and advice to feed the baby with infant formula. Design: A cross-sectional study. Setting: The current study covered twelve counties/districts in China. Participants: 5112 mothers with infants aged 0–5·9 months. Results: About 16 % of the mothers received free samples of infant formula. During pregnancy, this likelihood was higher among mothers in small and medium cities (OR: 1·96; 95 % CI 1·14, 3·38) and non-poor rural counties (OR: 4·65; 95 % CI 1·65, 13·14) compared with mothers in big cities. During the hospital stay, it was lower in big cities. After discharge, it was lower in poor rural counties (OR: 0·14; 95 % CI 0·05, 0·41). About 26 % of the mothers were advised to feed their infants with infant formula. The likelihood of receiving advice to feed the baby with infant formula from hospitals was lower in non-poor (OR: 0·37; 95 % CI 0·21, 0·66) and poor rural counties (OR: 0·35; 95 % CI 0·13, 0·91) than in big cities. Mothers in non-poor rural counties were less likely to receive advice from traditional mass media (OR: 0·17; 95 % CI 0·06, 0·48), while mothers in small and medium cities were more likely to receive advice from modern mass media (OR: 1·84; 95 % CI 1·20, 2·80) compared with mothers in big cities. Conclusions: The promotion strategy of infant formula varies from different places of residence in China. The study suggests the need to strengthen enforcement of relevant regulations, especially within health facilities and through modern mass media.